The Role of Teamwork, Interpersonal Communication and Work Motivation in Teacher Performance - Ahmad Baihaki (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The aim of this study was to determine the effect of teamwork of teachers, interpersonal communication and work motivation on their performance. This research was conducted at a private high school in Pamekasan Madura, Indonesia. This research applies the Survey Method using a questionnaire to collect data from these research variables. The research hypothesis was tested with the Path Analysis Technique used to investigate the direct and indirect influence of these variables on Teacher Performance. This research has several findings that Teacher Teamwork, Teacher Interpersonal Communication and Teacher Work Motivation have a direct positive effect on Teacher Performance while Teacher Teamwork and Teacher Interpersonal Communication also have an indirect positive effect on Teacher Performance through Teacher Work Motivation. This research recommends that improving Teacher Performance will be more effective by directly strengthening Teacher Teamwork, Teacher Interpersonal Communication and Teacher Work Motivation.